2016
DOI: 10.1515/folmed-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as a Novel Class of Potential Diagnostic Biomarkers in Neuropsychiatric Disorders

Abstract: Neuropsychiatric diseases, such as schizophrenia, bipolar disorder (BD), major depressive disorder (MDD) and autism spectrum disorder (ASD), are a huge burden on society, impairing the health of those affected, as well as their ability to learn and work. Biomarkers that reflect the dysregulations linked to neuropsychiatric diseases may potentially assist the diagnosis of these disorders. Most of these biomarkers are found in the brain tissue, which is not easily accessible. This is the challenge for the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 101 publications
(109 reference statements)
0
17
0
Order By: Relevance
“…miRNAs, which are short, noncoding sequences that typically regulate gene expression by suppressing protein coding mRNA, have been demonstrated to be biomarkers for several psychological disorders, including schizophrenia, major depressive disorder, and bipolar disorder (Kichukova, Popov, Ivanov, & Vachev, 2016; Maffioletti et al, 2016; Schmidt, Keck, & Buell, 2015). Within the central nervous system, miRNA are considered to play a major role in gene expression regulation (Kuss & Chen, 2008; Martinetz, 2016); however, the specific role of miRNAs in PTSD remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs, which are short, noncoding sequences that typically regulate gene expression by suppressing protein coding mRNA, have been demonstrated to be biomarkers for several psychological disorders, including schizophrenia, major depressive disorder, and bipolar disorder (Kichukova, Popov, Ivanov, & Vachev, 2016; Maffioletti et al, 2016; Schmidt, Keck, & Buell, 2015). Within the central nervous system, miRNA are considered to play a major role in gene expression regulation (Kuss & Chen, 2008; Martinetz, 2016); however, the specific role of miRNAs in PTSD remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al 11 reported that hypermethylation of the enolase 2 (ENO2) gene is present in 15% of patients with ASDs. It is noteworthy that microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), which play important roles as transcriptional and/or posttranscriptional regulators, [12][13][14][15][16][17][18][19][20] have also been implicated in ASDs and other neurological disorders. Some prominent functional studies have shown that lncRNAs perform a wide variety of functions, including participating in the recruitment of chromatin modifying complexes, providing a scaffold for the assembly of protein complexes, modulating alternative splicing, and employing enhancer-like functions.…”
mentioning
confidence: 99%
“…A rapid and inexpensive ddPCR has been developed that continuously monitors a patient's health status at a low cost (about one‐tenth of a new generation of sequencing methods) . Compared with the miRNA quantitation performed by ddPCR and real‐time PCR, ddPCR offers many potential advantages, including the ability to obtain absolute quantitation without external references, and has higher accuracy and improved reproducibility …”
Section: Discussionmentioning
confidence: 99%
“…39 Compared with the miRNA quantitation performed by ddPCR and real-time PCR, ddPCR offers many potential advantages, including the ability to obtain absolute quantitation without external references, and has higher accuracy and improved reproducibility. 95 With the further development of molecular biology, circulating miRNA combined with other molecular biological detection techniques may become sensitive and specific indicators of various clinical diseases with a wide range of clinical application.…”
Section: Challenges Of Circulating Mirna As a Biomarkermentioning
confidence: 99%